Pre-Wedding Education for Teenagers: Science Literacy, Character and Morals - Megawati Naibaho; Blasius Superma Yese; Sergius Lay; Bartolomeus Sihite; Ardiana Waruwu (Postgraduate, University of Mataram, 2025)
Adolescents are at an emotionally unstable age and need social recognition and self-existence. Biologically, adolescents experience significant development of sex hormones such as testosterone and progesterone, leading to an increased attraction to the opposite sex. Socially, adolescents are highly vulnerable to entering the youth community and engaging in various juvenile delinquency activities. Therefore, sex education is necessary for adolescents to prevent promiscuity and prepare them for marriage. This study explores the importance of scientific knowledge and character in strengthening loyalty to their marriage vows. The research applies a survey method. Quantitative data are obtained from the results of the questionnaire. Data collection through personal interviews and group meetings with young people and families in St. Boniface Parish, Alasa, and Christ the King Gidӧ Parish are useful factors in this study. The data obtained were analyzed descriptively. The result showed science education, character and moral values, especially husband and wife morals, are fundamental in maintaining the sanctity of marriage. The virtues of life, especially morals, encourage a person to behave appropriately and correctly by applying moral values. Morality is defined as personal or cultural values, codes of ethics, or social customs that establish rules about right and wrong.